What do medical outpatients attending a neurology clinic think about antidepressants? - Stone, J; Durrance, D; Wojcik, W; Carson, A; Sharpe, M (2004)
OBJECTIVE: To determine how medical outpatients attending a neurology clinic view antidepressant medication and whether those who present with medically unexplained symptoms have different views than those whose symptoms are explained by neurological disease. METHODS: A total of 89 consecutive outpatients attending a medical neurology clinic were interviewed. RESULTS: Those who believed that antidepressants were addictive comprised 74% and those who thought that they could cause physical harm comprised 47%. Only 49% were aware that antidepressants could be used to treat symptoms other than depression. The views of patients whose symptoms were rated by the doctor as being 'not at all' only 'somewhat' unexplained by neurological disease (37% of the total) were neither substantially nor statistically different those whose symptoms were rated as 'largely' or 'completely' explained by neurological disease. CONCLUSION: The majority of medical patients attending a neurology clinic, and not just those with medically unexplained symptoms, have largely negative beliefs about antidepressant drugs. The implications for patient adherence to these agents and for medical practice are discussed.